Meningiomas. - McDermott, Michael W. (Handbook of clinical neurology, 2020)
"Meningiomas, Volume 169, Part One, serves as a comprehensive review of the neurosurgical issues surrounding this extremely common brain tumor. Few procedures in surgery are more immediately formidable than an attack upon a large tumor of this type. In this volume of the Handbook of Clinical Neurology, experts in the field - from basic scientists to skilled neurosurgeons - have provided up-to-date synopses of each topic as it relates to this class of tumor. Surgical and radiation therapy, which remain the mainstays of treatment, are a major focus, but coverage also includes potential molecular avenues for the development of effective medical treatments"--Publisher's description